Progression of continuous downstream processing of monoclonal antibodies: Current trends and challenges. Issue 12 (18th October 2018) - Somasundaram, Balaji; Pleitt, Kristina; Shave, Evan; Baker, Kym; Lua, Linda H. L.
Abstract: Rapid advances in intensifying upstream processes for biologics production have left downstream processing as a bottleneck in the manufacturing scheme. Biomanufacturers are pursuing continuous downstream process development to increase efficiency and flexibility, reduce footprint and cost of goods, and improve product consistency and quality. Even after successful laboratory trials, the implementation of a continuous process at manufacturing scale is not easy to achieve. This paper reviews specific challenges in converting each downstream unit operation to a continuous mode. Key elements of developing practical strategies for overcoming these challenges are detailed. These include equipment valve complexity, favorable column aspect ratio, protein‐A resin selection, quantitative assessment of chromatogram peak size and shape, holistic process characterization approach, and a customized process economic evaluation. Overall, this study provides a comprehensive review of current trends and the path forward for implementing continuous downstream processing at the manufacturing scale. Abstract : Rapid advances in intensifying upstream processes for biologics production have left downstream processing as a bottleneck in the manufacturing scheme. Biomanufacturers are pursuing continuous downstream process development to increase efficiency and flexibility, reduce footprint and cost of goods, and improve product consistency and quality. Even after successful laboratory trials, the implementation of a continuous process at manufacturing scale is not easy to achieve.